The Corrosion Behavior of Different Gauges of Stainless Steel Wire Use in Removable Partial Denture and Orthodontics Appliances - Mansoor, N. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Wires are commonly used for the construction of orthodontic appliances and occasionally as wrought clasps and rests on partial dentures. The corrosion resistance is the most important properties of dental alloy. Corrosion process reported to cause a numerous adverse effects on both living tissue and restoration .The conditions in the mouth are very suitable for the occurrence of corrosion. The main objective of this study was to evaluate the corrosion behavior of different gauges of stainless steel wire in artificial saliva .Four gauges of dental stainless steel wire used in orthodontic and removable partial denture were used in this study 0.6mm.,0.7mm.,0 .8mm.&1.0mm.).The specimens were divided according to gauge in to four groups(A,B,C,&D ) ,ten specimens in each group .Each wire was cut by using wire cutter to get wire with (1cm) in length .Artificial saliva of Fusayama Meyer type was used as the testing solution .Sensitive electronic balance was used to weight the sample before immersion in solution and recording the results.This this represents the first weight(W1).Each specimen was put inside a test tube , and held using dental floss in a way that the specimen was fully immersed in the solution from all sides . The specimens then were put inside an incubator ,which was adjusted at 37Â±2 and left for 14 days .At the end of immersion period ; the specimens were removed from the solution and then allowed to dry and were balanced then the results were recorded .This represents the second weight (W2) .After obtaining the (W1)&(W2) the corrosion rate was calculated . The results before and after immersion showed that the 0.6 mm.& 0.7mm stainless steel wire gave the highest and more corrosion resistance value than 0.8mm&1.0mm.stainless steel wire . The result showed there is a statistical significance between (W1&W2) of 0.8mm stainless steel wire and highly significant between (W1&W2) of 1.0mm. stainless steel wire . The comparison of the results after calculating results in corrosion rate formula showed that the 1.0mm stainless steel wire more corrosion resistance followed by 0.8mm wire ,from 0.6mm& 0.7 mm wire .